Peningkatan Keterampilan Menulis Permulaan bagi Anak Cerebral Palsy Melalui Media Pembelajaran Berbasis Aplikasi Whatsapp - Lase, Vasas E.; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2022)
This research describes the improvement of learning Skills write start for child cerebral palsy class I through learning media based application whatsapp , which is based on the problems found by researchers in the children's field cerebral palsy child look difficult doing teacher's orders for To do activity write start even though activity this is activity important for child for smoothness child in write . Class I this there is one person which initials M classification of cerebral palsy . The process in teacher learning During this in the learning process the teacher provides guidance or help by direct to child in activity write , teacher helps child in hold tool write or pencil , teacher asks child for write member mentioned body by teacher, with show picture from member body that . Teacher too ask child for connect line break up , however with the long method this given not enough varied and not enough interesting attention child. Study this have destination for see process skill learning write start with using -based media application whatsapp and see is with use based media apps whatsapp could the occurrence of skills improvement write start for child Class I cerebral palsy. This study uses the type of classroom action research (CAR). Where this research is divided into two cycles, each cycle consists of: planning, action, observation and reflection. The results of this study are described in the form of a narrative that is equipped with graph of the results of increasing learning write start. implementation in cycle I child earn results M 40% The implementation in the second cycle of children obtained M 75% results. From the acquisition of the results can be concluded that there can be an increase in learning Skills write start for child Class I cerebral palsy with using -based media application whatsapp at State SLB Gunungsitoli